Simulation and FEM Analysis of Applied Force Effects for Energy Harvesting in Piezoelectric Bimorph Device - Panapong Songsukthawan; Chaiyan Jettanasen (My University, 2015)
Using of clean or renewable energy to generate electric power instead of fossil fuel is further promising. Smart material which can collect the dissipated vibration energy from moving object and transfer to electrical power called “Piezoelectric” material has developed and become increasingly interested. There are many kinds of synthetic material having piezoelectric effect; each type has different electrical and structural output when applying the same input. The structure analysis based on finite element method (FEM) is carried out in order to identify the optimized point of input force which will not damage the piezoelectric structure. The output voltage can be also determined. Moreover, the total displacement, equivalent stress and strain will be calculated and presented as contour mapping using ANSYS Workbench. The results are satisfactory and useful to identify material’s characteristics appropriated to specific task and also reduce times and cost of trial and error phase in experiment.
Keywords: Workbench; Electric potential energy; Energy transformation; Innovative Energy Harvesting Technologies